Gender analyses on the vulnerability types suffered by poor and older freshwater fisheries community members in Peninsular Malaysia - Saidi, Norehan; Zainalaludin, Zumilah; Jamaluddin, Askiah (Human Resource Management Academic Research Society, 2021)
This paper aimed to measure the vulnerability type that predicts the likelihood of the respondents in poor category of household income by sex-disaggregated data. The respondents were sampled in Peninsular Malaysia (n=322)). They suffer from at least one out of six types of vulnerability asked in the questionnaire. HO1 (no type of vulnerability predicts male in poor category of household income), and HO2 (no type of vulnerability predicts male in poor category of household income) were tested through Binary Logistic Regression (BLR) Model respectively and rejected. Both models were fit and significant (p<0.05) to predict the male and female respondents in poor category of household income. BLR Model 1 (male respondents) significantly predicted Handicapped Male and Single Father, with 3.60 times and less than 93.9 percent of the likelihood respectively for them to be in poor category of household income. For BLR Model 2 (female respondents), Single Mother and Handicapped Women predicted 16.15 times and 72.5 percent less of the likelihood respectively for them in the poor category of household income. This paper concludes the vulnerable women are poorer than the vulnerable men, and the handicapped men and single mothers are the poorest in freshwater fisheries communities.